The Transmission Mechanism of Bilateral Relationship Between Exports and Economic Growth in Vietnam - Cong, Phan The; Hiep, Nguyen Quang (International Journal of Economics and Financial Issues, 2017)
This article uses the vector error correction model (VECM) to analyze the transmission mechanism of bilateral relationship between exports and economic growth in Vietnam over the period 1999-2014. The results show that: (1) Existing bilateral relationship between exports and economic growth in Vietnam through the transmission channel in both short and long term; (2) Exports growth has been the motivation for economic growth and the resource factors play an important role in the transmission of the effects of exports to economic growth of Vietnam; (3) Economic growth also contribute to export growth by improving competitiveness in international trade through increasing productivity. Keywords: Economic growth, export, The Virtuous Circle Model, Verdoorn's Law. JEL Classifications: A12, G01, F43